PERANCANGAN SISTEM INFORMASI SEKOLAH PADA SD MASEHI 1 KABANJAHE BERBASIS WEB - Br Brahmana, Riana; Harianja, Eva Julia G.; Nainggolan, Rena (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
School Information Systems play an important role in managing administrative information in educational institutions. Masehi 1 Kabanjahe Elementary School still uses manual methods in collecting student data and collecting tuition fees. The manual method makes the work less effective and efficient. This study aims to develop a web-based School Information System for SD Masehi 1 Kabanjahe to improve efficiency in processing student data and administering tuition payments. This research uses a structured system development approach and a web-based system development methodology. The results of the School Information System research at the Web-Based Masehi 1 Kabanjahe Private Elementary School are expected to help meet the needs in processing student data and administrative data on tuition payments.